2009
DOI: 10.1111/j.1469-7580.2008.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic not monoaminergic fibers profusely innervate the young adult human testis

Abstract: Numerous studies have reported that intratesticular nerves exert important regulatory effects on the functions of the male gonad; however, as yet little is known about their distribution in the young adult human testis. The purpose of this study was to explore whether peptidergic and adrenergic nerves occur in the male gonad of this age, and, if present, to depict their distribution further. Thirty testes were collected from 15 reproductively healthy donors aged 21-32 years. Antibodies against protein gene pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
(115 reference statements)
1
12
0
Order By: Relevance
“…Our immunohistochemical investigation highlights that the PACAP/receptors system is well represented in the Coturnix testis. Indeed, PACAP is evident in Leydig and vascular endothelial cells, as well as in peritubular cells and in interstitial nervous fibers, as other neuropeptides previously described (Gong et al, ); by contrast, germ and Sertoli cells are lacking in PACAP. Furthermore, in Leydig cells, PAC 1 , VPAC 1 , and VPAC 2 are well represented too, in germ and Sertoli cells only VPAC 2 is recognizable.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our immunohistochemical investigation highlights that the PACAP/receptors system is well represented in the Coturnix testis. Indeed, PACAP is evident in Leydig and vascular endothelial cells, as well as in peritubular cells and in interstitial nervous fibers, as other neuropeptides previously described (Gong et al, ); by contrast, germ and Sertoli cells are lacking in PACAP. Furthermore, in Leydig cells, PAC 1 , VPAC 1 , and VPAC 2 are well represented too, in germ and Sertoli cells only VPAC 2 is recognizable.…”
Section: Discussionsupporting
confidence: 72%
“…In mammals, it is well known that circulating PACAP contributes to the intratesticular pool (Banks, Kastin, Komaki, & Arimura, ; Thomas et al, ) and that PACAP is expressed, even if transiently, in the seminiferous tubules during rat spermatogenesis (Kononen, Paavola, Penttilä, Parvinen, & Pelto‐Huikko, ). So, one can hypothesize that in Coturnix PACAP could be partly synthesized within vascular endothelial cells and then transferred to the Leydig cells and partly may be transported in the testis via nervous fibers, as occurs with VIP and NPY neuropeptides in human testis (Gong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hypothalamic‐pituitary‐gonadal axis, the nervous system may play a key role in Leydig cell function. Previous studies have shown that some nerve fibres reach the rat and human testes and may have an effect on Leydig cells 1,2 . The destruction of testicular innervation led to Leydig cell apoptosis and impaired Leydig cell function 1 .…”
Section: Introductionmentioning
confidence: 99%
“…These nerves extend throughout the tunica vasculosa, follow the interlobular septa, and end in the testicular interstitium. Most of the nerve fibers are peptidergic [99], 4.33,4.34).…”
Section: Nervesmentioning
confidence: 99%